If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -8 = 30x + 7 Reorder the terms: -8 + 5x = 30x + 7 Reorder the terms: -8 + 5x = 7 + 30x Solving -8 + 5x = 7 + 30x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-30x' to each side of the equation. -8 + 5x + -30x = 7 + 30x + -30x Combine like terms: 5x + -30x = -25x -8 + -25x = 7 + 30x + -30x Combine like terms: 30x + -30x = 0 -8 + -25x = 7 + 0 -8 + -25x = 7 Add '8' to each side of the equation. -8 + 8 + -25x = 7 + 8 Combine like terms: -8 + 8 = 0 0 + -25x = 7 + 8 -25x = 7 + 8 Combine like terms: 7 + 8 = 15 -25x = 15 Divide each side by '-25'. x = -0.6 Simplifying x = -0.6
| -7x+3=2x+-1 | | 9r+2=65 | | -31-(-8.6)= | | 18-3.8t=7.36-1.96 | | 5(2x+5)=-35+30 | | 6m-1=5m-2 | | 2a+b=15.7 | | 18-3.8t=7.36-1.98 | | -3-4x=-5x | | (2k-4)x+(4k+6)y+(3q-2)=0 | | 3x-2.8=4.2-4x | | 9x+6x+4=114 | | 37=5 | | (2k-x)x+(4k+6)y+(3q-2)=0 | | 15.3-(-11)= | | 4(x-8)+x=26 | | 4(1+w)=3(4+w) | | -4+5+6v=1+5v+3 | | 3(c+4)=5+2c | | (4x-1)+(2x+1)=8x-4 | | 3i^2+15/6-3i | | 7(x-1)=6x | | x^2+15/6-x | | 3z+3-z=10+z-5 | | 36=2(3.14)r | | 3x-13=2x | | 7g+1-5g=-8 | | -X^2-12X-20=0 | | 73.14/23 | | x/3+12/1=-x/3 | | -[5z-(15z+6)]=6+(9z+0) | | (-11-16)+5= |